GLOBALIZATION AND GLOBAL GOVERNANCE - A. A. Gromyko (Vestnik MGIMO-Universiteta)
Anatoly Andreevich Gromyko, a professor of the Moscow State University, a corresponding member of the Russian Academy of Sciences reflects in his article on the destinies of mankind and the most complex problems facing the world community at the early 21 century under globalization and increased demand in global governance. In his analysis the author concedes that after numerous pieces of research on various aspects of these two phenomena, there are still more questions than answers. He believes that globalization might become a force serving not only private interests of big corporations but also the common good of humanity. Since interdependence is the main feature of our world we should not fall prey to the ideal images of global governance because there is no one size fit all global governance. The article elaborates the three most pressing world problems:– the need in a new way of thinking about globalization. According to the author the problems of globalization must be approached with knowledge of history and acknowledgement of social justice;– the need in morally acceptable balance among unifying potential of globalization, unchained global market and the state as the last resort of its nation;– the need to make United Nations a platform, where political and social democracy should lay ground for global governance so craved for by the mankind. The author pays special attention to the dichotomy between the force of law and the law of force as well as to the prospects for the new democratic global order accommodating the sustainable development of human civilization.